The MicroRNA miR-696 is regulated by SNARK and reduces mitochondrial activity in mouse skeletal muscle through Pgc1α inhibition - André L. Queiroz; Sarah J. Lessard; Amanda T. Ouchida; Hygor N. Araujo; Dawit A. Gonçalves; Dimitrius Santiago P. Simões Fróes Guimarães; Bruno G. Teodoro; Kawai So; Enilza M. Espreafico; Michael F. Hirshman; Luciane C. Alberici; Isis do Carmo Kettelhut; et al. (Elsevier, 2021)
Objective: MicroRNAs (miRNA) are known to regulate the expression of genes involved in several physiological processes including metabolism, mitochondrial biogenesis, proliferation, differentiation, and cell death. Methods: Using "in silico" analyses, we identified 219 unique miRNAs that potentially bind to the 3'UTR region of a critical mitochondrial regulator, the peroxisome proliferator-activated receptor gamma coactivator (PGC) 1 alpha (Pgc1α). Of the 219 candidate miRNAs, miR-696 had one of the highest interactions at the 3'UTR of Pgc1α, suggesting that miR-696 may be involved in the regulation of Pgc1α. Results: Consistent with this hypothesis, we found that miR-696 was highly expressed in the skeletal muscle of STZ-induced diabetic mice and chronic high-fat-fed mice. C2C12 muscle cells exposed to palmitic acid also exhibited a higher expression of miR-696. This increased expression corresponded with a reduced expression of oxidative metabolism genes and reduced mitochondrial respiration. Importantly, reducing miR-696 reversed decreases in mitochondrial activity in response to palmitic acid. Using C2C12 cells treated with the AMP-activated protein kinase (AMPK) activator AICAR and skeletal muscle from AMPKα2 dominant-negative (DN) mice, we found that the signaling mechanism regulating miR-696 did not involve AMPK. In contrast, overexpression of SNF1-AMPK-related kinase (SNARK) in C2C12 cells increased miR-696 transcription while knockdown of SNARK significantly decreased miR-696. Moreover, muscle-specific transgenic mice overexpressing SNARK exhibited a lower expression of Pgc1α, elevated levels of miR-696, and reduced amounts of spontaneous activity. Conclusions: Our findings demonstrate that metabolic stress increases miR-696 expression in skeletal muscle cells, which in turn inhibits Pgc1α, reducing mitochondrial function. SNARK plays a role in this process as a metabolic stress signaling molecule inducing the expression of miR-696.